PENGARUH NILAI PELANGGAN DAN KEPUASAN TERHADAP LOYALITAS ANGGOTA CREDIT UNION KELING KUMANG PONTIANAK - S, Yuana; Barata, Juliahir (Jurnal Ekonomi Integra, 2023)
This study entitled "The Influence of Customer Value and Satisfaction on the Loyalty of Members of the Keling Kumang Pontianak Credit Union. The design used in this research is descriptive and causal design using multiple linear regression. The sample in this study was determined by 100 respondents. The criteria for determining the population are members of the Keling Kumang CU who have been members for at least 5 years, this is so that the selected respondents have historical experience and can assess related to customer value, satisfaction and loyalty. The results of the research analysis are as follows: customer value and satisfaction have a significant effect on the loyalty of respondents as members of the CU. Rivet Kumang Pontianak. Customer value has a significant effect on respondent loyalty as a member of CU. Rivet Kumang Pontianak. satisfaction has a significant effect on respondent loyalty as a member of CU. Rivet Kumang Pontianak. The magnitude of the influence of the customer value and satisfaction variables on the ups and downs of the value or variation of the loyalty variable is 30.60% while 69.40% is influenced by other variables besides the variables in this study.